Non-pharmacological interventions for the prevention of postoperative ileus after gynecologic cancer surgery - Kemal Gungorduk; Isa Aykut Ozdemir (Elsevier, 2021)
Postoperative ileus (POI) is characterized by impaired gastrointestinal motility after surgery. POI is a major concern for surgeons because it increases hospital stay, the cost of care, and postoperative morbidity in patients who have undergone extensive gynecological oncological surgery. Although several interventions have been proposed and investigated, no effective treatment for the prevention and management of POI has been established. The present review summarizes the current evidence on non-pharmacological interventions, including coffee consumption and chewing gum, used to prevent and treat POI. We obtained studies from MEDLINE, Cochrane Database of Systematic Reviews, ISI Web of Science, and SCOPUS databases.